(untitled) (Journal of Parents and Teachers, 2025)
Maisie, a young orphan, immerses herself daily in stories of sea monsters and hunters from her books. One night, she decides to escape from her bedroom and experience the world for herself. After the ship’s captain refuses to let her join future sea monster hunts, she manages to stow away on the ship of her dreams—unaware that what she read in those stories might not be entirely true. She embarks on a journey carrying deep prejudices about monsters, viewing them as evil and bloodthirsty enemies, without considering that they might actually have kind hearts. Perhaps these creatures are simply defending their home. Maisie comes to understand the importance of developing a critical view of history and reality, as well as her right to a family that will care for and protect her. This film invites us to reflect on the absurdity of war and the economic and political interests that often lie behind it. It presents an alternative version of a reality that is, unfortunately, sometimes distorted.